Local Democratic School: Community Social Training for Improving the Quality of Democracy - Tina Cahya Mulyatin; Teguh Anggoro; Tofan Ibrahim (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The lack of awareness and knowledge among the Banjar community regarding government participation and transparency led to the implementation of the community service activity at the Local Democratic School. The purpose of this community service is to provide education to the community about democracy and governance. The community service method, using the participatory action research approach, began with an initial survey, focus group discussions, and training targeting KPU partners, attended by 25 participants serving as the Election Committee in each village or neighborhood across Banjar City. Through a series of concrete and collaborative steps, it is expected to establish a stronger foundation for inclusive and sustainable democracy at the local level, enhancing community involvement and contribution to positive changes in social structures and public policies. The duration of this PkM activity is seven months, from March to September 2023. The outcomes of the activity received positive feedback from the community, with a 91% response rate from participants indicating an understanding of various topics covered, including local content, governance, civil society, gender and democracy, welfare state, Pancasila democracy, sociopreneurship, law and human rights, and citizen participation in government. The implication is that this program can enhance community understanding and involvement in creating positive changes in social structures and public policies at the local level.